Physico-chemical properties and characterization of thermophilic flora from button mushroom compost prepared using SMS of different mushroom as supplement - Thakur, Abha; Gupta, Dharmesh; Kumar, Anil; Kamal, Shwet; Thakur, Diksha; Sharma, Pratibha; Reetu (Mushroom Research, 2024)
The white button mushroom (Agaricus bisporus) is widely cultivated worldwide using a substrate composed of wheat straw, horse manure, chicken manure, gypsum, and urea. In this study, spent mushroom compost was also used in varying quantities for button mushroom compost preparation. Compost preparation occurs in two phases, both significantly involving thermophilic fungi. These fungi affect the growth of mushroom mycelia and mushroom yield in three distinct ways i.e. they reduce the concentration of ammonia in the compost, immobilize nutrients in a form that is apparently available to the mushroom mycelia and support the overall composting process. Four fungal species were isolated from the compost samples using the serial dilution method and were further identified by the National Centre of Fungal Taxonomy, New Delhi. The four species associated with Agaricus bisporus compost formation are Aspergillus niger, Aspergillus fumigatus, Scytalidium thermophilum, and Torula compostis. Scytalidium thermophilum dominated the fungal biota of the compost, while Torula compostis, a newly identified species, plays a significant role in the first phase of composting.